The construct “limit” and anomalous experiences in psychics - Parra, Alejandro (2018)
This study aims at distinguishing self-named psychics (or clairvoyant) from a control group (non-psychics) considering the variable “ frequency of unusual perceptual experiences” (anomalous perception), and the psychological construct “limit”. Participants were divided into psychics and non-psychics (people who had psychic experiences but no extrasensory capacities). Both psychics (N = 87) and the control group (N = 112) completed the Cardiff Anomalous Perceptions Scale (CAPS), the Revised Transliminality Scale (RTS), the Limits Questionnaire, and a scale to measure their psychic abilities. All the hypotheses were confirmed: psychics had higher scores on transliminality, anomalous perception and “fine limit” in comparison with non-psychics. In addition, the variable “anomalous experiences” was the best predictor for the psychics group (β = .073; p = .03), followed by the variable “fine limit”. Psychics would be those who were able to pass the “continuity hypothesis” of Hartmann’s limit due to their familiarity with their own capacity to alter their conscience.